Apart : production design - Sadik Ismail (2018)
Film speaks to us in the form of visuals. This visual language is captured by the world that is created within the frame that the lens of the camera captures. Herein lies the responsibility of the production designer; to visualise and synthesise the script. This report documents my ideation, process and creation of this unique visual world; as the production designer for, young nights, a final year thesis film. This being my first foray into the world of a production designer. It was a huge task to take on plunging in head on with very little prior knowledge into the technicalities of the role. It was a role I had to grow into. Having an interest and learned knowledge on interior design certainly benefited me to a certain extent but having the mind to imagine and the propensity to execute are very different things. What I garnered quickly was that, the role of a production designer is very much like that of a director; hence the often interchangeably used term: Art director. As a production designer, my role is to envision and to direct the people that execute - set designers, wardrobe stylist, graphic designers, art assistants, etc.